Religions for Peace or Religions of Peace? Some Reflections on the Trends in the Development of Interreligious Dialogue - S. V. Melnik (Концепт: философия, религия, культура, 2022)
Today, in the increasingly entangled, interdependent, and digital world, religion is still of utmost importance, and for some societies around the world its role is critical. The new reality poses novel challenges: issues we face today call for the investigation into current trends in the dialogue of religions. In this way, followers of various religions that would be willing to cooperate to solve major problems of religious diversity would have reference points to compare themselves with. Concerning the goals and objectives of social development, scientific analysis needs to study conceptual foundations and the most effective strategies for interreligious dialogue and communication. To that end, a case study of interreligious contacts and the newest trends serves this objective best. The article is devoted to studying the experience of a global interreligious dialogue, precisely the so-called religion of peace phenomenon with an emphasis on peace and prosperity. One of the most common practices of the religion of peace is joint prayers of members of different religions has entered the agenda of international forums on religion. An important source of information for the study was the author's first-hand experience of participating in interreligious events, including the 10th Assembly of the largest interreligious organization Religions for Peace (Lindau, Germany, 2019). Four main types of interreligious dialogue are described — polemical, cognitive, peacemaking, and partnership. It is noted that partnership and peace-making types dominate modern intercultural dialogue: helping the underprivileged, maintaining moral values and justice, integrating migrants, protecting the environment, etc. At the same time, the significance of polemical and cognitive (theological) types fades. Thus, the author concludes that intercultural dialogue is becoming a tool for increasingly peaceful coexistence of religions as social institutions, and therefore increases their positive social influence.